Comparison of the Relationship Between SI and RASI Scores With the Outcome of Sepsis Patients - Hashemian, Amir Masoud; Baghshani, Zahra; Farzaneh, Roohie; Zamani Moghadam, Hamid; Maleki, Fatemeh; Bagherian, Farhad; Ahmadnezhad, Somayyeh; Foroughian, Mahdi (Frontiers in Medicine, 2022)
The aim of this study was to compare the relationship between shock index (SI) and respiratory adjusted shock index (RASI) scores with the final outcome of sepsis patients referred to the emergency department. This was a prospective research that examined at individuals who had been diagnosed with sepsis, determined by the presence of at least two of the three quick sepsis-related organ failure assessment (qSOFA) criteria ‎and the presence of an infectious disease based on a diagnosis made.Demographic information of patients, SI score, RASI score, and information related to the patient's clinical symptoms were recorded in the checklist.. Data analysis was performed using descriptive and inferential tests. In the present study, a total of 178 patients, 46 patients (25.8%) were transferred to intensive care unit, 98 patients (55.1%) were admitted to the normal wards. 85 patients (47.75%) died and the mean length of hospital stay of all patients was 11.07±9.23 days. 44 patients (24.7%) had referred with a decreased level of consciousness and 44 patients (24.7%) presented with confusion. Survival distribution was not statistically different for the four defined groups (based on statistical quartiles (P = 0.320). Receiver operator curves were considered as the date of death in the case of the deceased and the date of discharge from the hospital in the case of the living as censored. The AUC of the RASI scoring system for predicting mortality was 0.614 (P = 0.009) while this value was not significant for SI (P = 0.152). In logistic regression analysis, it was found that by adjusting for the variables of age, sex, sepsis etiology, blood pressure and heart rate, level of consciousness, and gender, patients with the lower respiratory rate (OR 1.6, z = -0.159 p = 0.007), younger age (OR 1.6, z = -0.029 p = 0.006) and higher RASI score are more in risk of mortality (OR 1.29, z = 1.209, p = .031). The results of our study showed that RASI scoring can be a good criterion for predicting the chance of mortality in patients with sepsis and is superior to previous criteria such as SI.